Migration. Comparing political and cultural visions - Michele Bruni; Mario Catani (Global Labor Organization (GLO), 2019)
Different interpretations of migration confront themselves in the political arena. Considering two factors, necessity and acceptability, the paper identifies four stereotyped visions: the society of the walls, the society of mercy, the society of ghettos, and the society of reason. The first three share the ideological assumption that migration flows are supply determined, that they are pushed by poverty, lack of jobs, and desperation due to the lack of perspectives of a better future. The fourth vision states, based on robust empirical evidence, that migrations are determined by the structural shortage of labour that characterizes an increasing number of Developed countries, in the presence of an unlimited supply of labour in the Least developed countries. The implication of this idea is that international migrations flows of increasing size are unavoidable and indispensable to both groups of countries that should reach a political agreement to jointly manage them with mutual advantage. An Annex -that summarize previous work of one of the author but is based on the last data and estimates released by UN DESA- provides a short, critical introduction to the concept of the demographic transition and present the statistical implications of its most relevant consequence: the demographic polarization of the plane.
Keywords: F22; J11; J24; 330; Migration; Demographic transition; Demographic polarization; Structural labour shortage; Structural excess of labour; Africa